2001
DOI: 10.1002/app.1381
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of poly(ethylene terephthalate) modified with codiols

Abstract: The nucleation of poly(ethylene terephthalate) (PET) by codiols and olefinic segments was studied. The codiols 1,5-pentanediol, 1,8-octanediol, 2,5-hexanediol, and 1,3-dihydroxymethyl benzene were copolymerized into PET in a concentration range of 0 -10 mol %. The melting (T m ), crystallization (T c ), and glass-transition (T g ) temperatures were studied. These codiols were found to be able to nucleate PET at low concentrations, probably by lowering the surface free energy of the chain fold. However, the cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…Of notable applicability to the present study, Bier et al5 found that PET copolymers containing ∼5 mol % of branched codiols, such as 2,5‐hexanediol and 3‐methyl‐2,4‐pentanediol, crystallized significantly more rapidly than PET homopolymer. In a related study, Bouma et al6 found that PET copolymers containing low concentrations of 1,5‐pentanediol, 1,8‐octanediol, 2,5‐hexanediol, or 1,3‐dihydroxymethyl benzene were able to enhance nucleation. Bouma et al6 found the optimum concentration of 2,5‐hexanediol to be 1 mol %, much lower than that suggested by Bier et al5 Likewise, it was shown that copolymers containing a branched olefinic diol (C 36 ‐diol) were also able to improve crystallizability.…”
Section: Introductionmentioning
confidence: 97%
“…Of notable applicability to the present study, Bier et al5 found that PET copolymers containing ∼5 mol % of branched codiols, such as 2,5‐hexanediol and 3‐methyl‐2,4‐pentanediol, crystallized significantly more rapidly than PET homopolymer. In a related study, Bouma et al6 found that PET copolymers containing low concentrations of 1,5‐pentanediol, 1,8‐octanediol, 2,5‐hexanediol, or 1,3‐dihydroxymethyl benzene were able to enhance nucleation. Bouma et al6 found the optimum concentration of 2,5‐hexanediol to be 1 mol %, much lower than that suggested by Bier et al5 Likewise, it was shown that copolymers containing a branched olefinic diol (C 36 ‐diol) were also able to improve crystallizability.…”
Section: Introductionmentioning
confidence: 97%
“…Poly(ethylene terephthalate) (PET) is widely used in many domains of synthetic fibers, liquid containers, thermoforming plastics, engineering resins, and textile and apparel industry [1][2][3][4] because of its superior properties such as better elasticity, higher strength, thermal stability, and other advantages. [5][6][7] However, some disadvantages of PET fibers such as low moisture regain, poor dyeability and antistatic property, rigid, and waxy handling [8][9][10] are mainly involved by the high regularity of molecular chains, high crystallinity, and low hydrophilicity, 11,12 which are hindering their further application in textile, fashion, and other industries.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ethylene terephthalate) (PET) has many outstanding properties for textile and industrial fiber applications, but it is difficult to dye because of its high crystallinity, marked hydrophobicity, and lack of chemically active groups 1–5. It is well known that copolymerization of polyesters with ionic groups constitutes a very effective method to improve both chemical and physical properties of the polymer 6, 7.…”
Section: Introductionmentioning
confidence: 99%